How do you solve 4p^2=-25p-25 using the quadratic formula?

1 Answer
Apr 11, 2018

-5 or (-5)/4

Explanation:

To use the quadratic formula our function has to be in the form:

a^2 + bx +c =0

So, let's start off by subtracting 4p^2 from both sides, to get it into that form. That gives us:

0 = -4p^2 -25p - 25

I'm also going to multiply both sides by -1, to eliminate all of the negatives. You don't have to do this, but it will make the process quite a bit cleaner. That leaves us with:

0 = 4p^2 +25p + 25

So, a = 4, b=25, c=25

Now we simply substitute our values into the quadratic equation

= (-b+-sqrt(b^2-4ac))/(2a)

= (-(25)+-sqrt((25)^2-4(4)(25)))/(2(4))

= (-25+-sqrt(225))/(8)

= (-25+-15)/(8)

= (-40)/(8) or (-10)/8

= -5 or (-5)/4